2021
DOI: 10.1093/ons/opab355
|View full text |Cite
|
Sign up to set email alerts
|

Qlone®: A Simple Method to Create 360-Degree Photogrammetry-Based 3-Dimensional Model of Cadaveric Specimens

Abstract: BACKGROUND Human cadavers are an essential component of anatomy education. However, access to cadaveric specimens and laboratory facilities is limited in most parts of the world. Hence, new innovative approaches and accessible technologies are much needed to enhance anatomy training. OBJECTIVE To provide a practical method for 3-dimensional (3D) visualization of cadaveric specimens to maximize the utility of these precious ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 17 publications
(18 reference statements)
1
56
0
Order By: Relevance
“…A possible solution to this limitation is to incorporate photogrammetry into building the models. Photogrammetry creates 3D representations using multiple 2D photographs of an object and has long been used in anatomy to bring 3D perception to 2D photographs or to create virtual 3D representations of anatomical specimens ( 1 , 5 , 10 , 36 – 38 ). De Benedictis et al ( 36 ) reported quantitative validation of photogrammetry for the study of white matter connectivity of the human brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A possible solution to this limitation is to incorporate photogrammetry into building the models. Photogrammetry creates 3D representations using multiple 2D photographs of an object and has long been used in anatomy to bring 3D perception to 2D photographs or to create virtual 3D representations of anatomical specimens ( 1 , 5 , 10 , 36 – 38 ). De Benedictis et al ( 36 ) reported quantitative validation of photogrammetry for the study of white matter connectivity of the human brain.…”
Section: Discussionmentioning
confidence: 99%
“…De Benedictis et al ( 36 ) reported quantitative validation of photogrammetry for the study of white matter connectivity of the human brain. Although their study used a relatively sophisticated setup, our group recently showed the applicability of a freely available 360° photogrammetry tool for neuroanatomy studies ( 1 ). In addition, Roh et al ( 5 ) also incorporated photogrammetry into a virtual 3D environment to create realistic texture details of cadaveric brain specimens, but their study lacked quantitative validity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we have implemented a well-known methodology such as photogrammetry used primarily in geography [ 4 , 5 ] or archeology [ 6 ] for the generation of authentic, cadaver-based, 3D models of layered dissection of the back muscles. So far, there are relatively few studies examining the use of photogrammetry in neurosurgery, mainly in skull base surgery, brain 3D models, and cadaver dissections [ 15 - 17 ]. Yet, the benefits of this technology are clearly visible: the possibility to create a very accurate dissection-based 3D model that can be rotated from every possible angle, magnified, and with each important anatomical structure indicated and referenced.…”
Section: Discussionmentioning
confidence: 99%